Two-coordinate group 14 element(ii) hydrides as reagents for the facile, and sometimes reversible, hydrogermylation/hydrostannylation of unactivated alkenes and alkynes. Issue 12 (1st October 2015) - Hadlington, Terrance J.; Hermann, Markus; Frenking, Gernot; Jones, Cameron
Abstract : The ambient temperature hydrometallations of a variety of unactivated alkene and alkyne substrates using two-coordinate hydrido-tetrylenes, :E(H)(L † ) (E = Ge or Sn; L † = extremely bulky amide), are reported. Abstract : Reactions of the solution stable, two-coordinate hydrido-tetrylenes, :E(H)(L † ) (E = Ge or Sn; L † = –N(Ar † )(SiPr i 3 ); Ar † = C6 H2 C(H)Ph2 2 Pr i -2, 6, 4), with a variety of unactivated cyclic and acyclic alkenes, and one internal alkyne, lead to the rapid and regiospecific hydrometallation of the unsaturated substrate at ambient temperature. The products of the reactions, [L † E(C2 H4 R)] (E = Ge or Sn, R = H, Ph or Bu t ), [L † ECH(CH2 )3 (CH2 ) n ] (E = Ge, n = 1, 2 or 3; E = Sn, n = 1) and [L † EC(Ph){C(H)(Me)], include the first structurally characterised examples of two-coordinate amido/alkyl germylenes and stannylenes. The cycloalkene hydrometallation reactions are cleanly reversible under ambient conditions, a process which computational and experimental van't Hoff analyses suggest proceeds via β-hydride elimination from the metal coordinated cycloalkyl ligand. Similarly, the reactions of :Ge(H)(L † ) with 1, 5-cyclooctadiene and 2-methyl-2-butene, both likely proceed via β-hydride elimination processes, leading to the clean isomerisation of the alkene involved, and its subsequent hydrogermylation, to give [L † Ge(2-cyclooctenyl)] and [L † GeC2 H4 C(H)Me2 ], respectively. Reactions of [L † GeEt] and [L † Ge(C5 H9 )] with the protic reagents, HCl, NH3 and EtOH, lead to oxidative addition to the germanium(ii ) centre, and formation of the stable chiral germanium(iv ) complexes, [L † Ge(C5 H9 )(H)Cl] and [L † Ge(Et)(H)R] (R = NH2 or OEt). In contrast, related reactions between [L † SnEt] and Bu t OH or TEMPOH (TEMP = 2, 2, 6, 6-tetramethylpiperidinyl) proceed via ethane elimination, affording the tin(ii ) products, [L † SnR] (R = OBu t or OTEMP). In addition, the oxidation of [L † Ge(C6 H11 )] and [L † Sn(C2 H4 Bu t )] with O2 yields the oxo-bridged metal(iv ) dimers, [L † (C6 H11 )Ge(μ-O)2 ] and [L † (Bu t C2 H4 )Sn(μ-O)2 ], respectively.